Efl learner’s perspectives about the teaching - learning process of English as a foreign language (EFL) in online Education - Constante Cruz, Denyse Ariana (2022)
This project analyzed the EFL Learners’ perspectives about English as a foreign language [EFL] teaching and learning in online education. The twenty-six EFL students belong to the sixth cycle of Pedagogy of National and Foreign Languages (English) career at the Technical University of Cotopaxi, which were randomly selected. Qualitative research was used initially to comprehend the problematic and a mixed methodology was applied, in which two phases of data collection were carried out. The quantitative phase applied an online survey using a Likert scale to obtain quantifiable data on the teaching-learning process of the English language in online education. For the qualitative part, semi-structured interviews with open-ended questions were used to gather information about the student’s perceptions and the factors that influence their learning of English in a virtual environment. Data analysis of the interview was performed by a bottom-up approach focused on coding, transcription, and subsequent division into three categories and six subcategories representing students’ views of the teaching-learning process in an online modality. On the other hand, for the analysis of the survey, the information was classified and related to the stated objective and the google forms tool was used to statistically extract the percentages for the analysis of results and discussion. Several factors interfere with the students’ language learning inside the online classroom such as methodologies employed, technological resources, level of communication, the time established for each activity, motivational factors. Thus, it is essential to apply artful methods, techniques and activities in the teaching-learning process, focusing on improving the learners’ language skills. The analysis of the interviews and the surveys provides guidelines for enhancing the use of the methods, learning platforms and resources in higher distance education regarding strengths and weaknesses of students. The beneficiaries will be the educational body since it will provide an informed approach of teaching English as a foreign language in a virtual classroom and the perspective of students regarding online learning.